Dramatizing Local History “Topekkong Agreement”: Its Effects on Stimulating the Students’ English Performance - Syukri, Muhammad (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The teaching of a foreign language, particularly English, is mandatory at the curriculum in Indonesia. This language has an important contribution to the development of science and technology. So, it needs to strategy and development to answer the challenges in there. The current study is how improving the students’ English performance through learning approach by using local history. The research was conducted in the second academic year, particularly 2nd semester with 20 students who enrolled in English speaking ii at Muhammadiyah institution in bone. The mixed method is used to find out the improvement of speaking achievement shows that dramatize with a particular approach such as local history effective to improve the students’ English performance. Furthermore, this research can be expected to recognize one of a pride local culture and encourage strong motivation for learning English as a medium in learning process. Using media drama is expected to draw interest in the learners because it will improve the ability and the achievement in their learning of English.